Turning Waste into Value: Biodecomposition of Oil Palm Trunk Biomass for Sustainable Compost Fertilizer Production - Nina Veronika; Sri Wahyuni; Nur Asma Deli; Hayatul Khairul Rahmat; Barokat Mamah (Nucleus Journal, 2026)
The rapid expansion of the oil palm industry has generated substantial biomass waste, particularly from oil palm trunks during replanting activities. Improper management of this waste can cause environmental problems, while its high lignocellulosic content offers potential for conversion into organic fertilizer. This study aimed to evaluate the feasibility of utilizing oil palm trunk waste as compost through a biodecomposition process. The compost was produced using a mixture of oil palm trunk biomass and organic additives, followed by physicochemical analysis to assess compost quality. The results showed that the compost contained C-organic levels ranging from 46.3% to 52.1%, C/N ratios between 20.2 and 21.9, pH values of 7.58–8.00, and total macronutrient content (N + P₂O₅ + K₂O) of 7.03–8.74%. All parameters met the quality standards for solid organic fertilizers according to SNI No. 7763: 2024. These findings indicate that oil palm trunk compost has good maturity and nutrient content, making it suitable for improving soil fertility and supporting sustainable oil palm replanting. The study highlights the potential of converting oil palm trunk waste into value-added organic fertilizer as part of a sustainable waste management strategy.